Biodiversity and Ecological Structure of Mangrove Mature in Coastal Area of Dumai District - Riau Province - EKO PRIANTO; RHOMIE JHONNERIE; RAMSES FIRDAUS; TAUFIK HIDAYAT; MISWADI MISWADI (Society for Indonesian Biodiversity, 2006)
This research in coastal area of Dumai has been completed in September untill Desember 2003. The aim of this research was to collect basic data of mangrove ecosystem which covered inventory of biodiversity and ecology structure by using primary and secondary data. Primary data of mangrove forest ecosystem has been collected by line transect method while secondary data was collected by study literature and previous study report. The result showed that there were 17 types of primary mangrove and 18 types of secondary mangrove. The main value indeks in every study area indicated that in the study area I and IV, Xylocarpus granatum had high value as 104,53 and 104,22 subsequently. In the study area II, III and V, Rhizophora apiculata had the high value which subsequently were 114,39, 108,81 and 110,19. There were two main extinct spesies of mangrove, which are Scyphiphora hydrophyllaceae (Cingam/Perepat Lanang) and Sonneratia ovata (Kedabu), in which exceptional management is needed for sustainability of these species.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Biodiversity, Ecological Structure, Dumai District.